2006
DOI: 10.1097/01.ico.0000183493.00884.8f
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless Amniotic Membrane Fixation Using Fibrin Glue for Ocular Surface Reconstruction in a Rabbit Model

Abstract: Our results demonstrate the general feasibility of reproducible and reliable sutureless amniotic membrane fixation onto the corneal surface in rabbits. Stable adherence is maintained until epithelialization is completed. The sutureless technique gives sufficient manipulation time for the sheet before the final cross-linking process is completed. Furthermore, several advantageous characteristics could be demonstrated as increased biocompatibility, better epithelialization pattern and the lack of membrane shrink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 35 publications
1
35
0
5
Order By: Relevance
“…Treatment includes mechanical debridement and flap reattachment. Successful cases of flap attachment has been reported with no recurrence of epithelial ingrowth or fluid accumulation in the interface [107][108][109][110]. Azar et al treated recurrent epithelial ingrowth after LASIK by attaching an annular AM graft with fibrin glue [111].…”
Section: Epithelial Ingrowth and Other Laser-assisted In Situ Keratomilmentioning
confidence: 99%
“…Treatment includes mechanical debridement and flap reattachment. Successful cases of flap attachment has been reported with no recurrence of epithelial ingrowth or fluid accumulation in the interface [107][108][109][110]. Azar et al treated recurrent epithelial ingrowth after LASIK by attaching an annular AM graft with fibrin glue [111].…”
Section: Epithelial Ingrowth and Other Laser-assisted In Situ Keratomilmentioning
confidence: 99%
“…[4][5][6][7][8] In addition, the outcomes of AMT using fibrin glue for corneal ulceration, perforation, and ocular surface reconstruction have been reported in clinical and experimental studies. [9][10][11][12][13] However, the results of pterygium surgery with AMT using fibrin tissue sealants have been evaluated in limited number of studies. Pfister and Sommers 14 were the first to report the use of fibrin glue for amniotic membrane grafting in two patients with primary and in one with recurrent pterygium.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings suggest that epithelialization may occur both over and under AM when sutures are used to secure the membrane to rabbit 11 or human 12 corneas. Therefore, one may wonder whether epithelialization may be influenced by transplanted AM if sutures are used.…”
mentioning
confidence: 99%
“…26 It has been shown that in contrast to suturing, epithelial growth takes place only over AM when fibrin glue is used for central epithelial defects in rabbit corneas. 11 Therefore, we wondered whether a different healing pattern would be observed in patients' eyes with partial LSCD if AM was secured by fibrin glue to the corneal and limbal surfaces following removal of conjunctivalized epithelium. To address these questions, we retrospectively reviewed our results of AM transplantation using fibrin glue in eyes with partial LSCD.…”
mentioning
confidence: 99%